Pergeseran Budaya Dari Rokok Konvensional Ke Rokok Elektrik Pada Customer Counter Vapor Kito Di Kota Palembang - Rizqullah, Muhammad Naufal; Maharani, Dwi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Abstract The development towards something more modern will definitely occur in human life which includes various aspects such as technology, knowledge, lifestyle, culture, and others. The problem of smoking is an issue that is still pro and contra in society. Therefore, many people choose to use certain methods during the transition period until they can be free from conventional cigarettes. The main purpose of the creation of electric cigarettes is to help smokers quit the habit of using conventional cigarettes. The formulation of the problem in this study is